Optimasi Pemanfaatan Tanaman Transgenik - , Sobir (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
Human effort on improving agricultural crops has been expanding very rapidly, and recently by using gene transformation technology it was possible to introduce genes from biologically unrelated organisms into plant genomes. Gene transformation technology, known as transgenic technology, has been successfully introduced gene encoding insecticidal compound from bacteria Bacillus thuringiensis into several crops, for example. Introducing new technology is offering several advantages but also brings several disadvantages however since the technology isImportant for maintaining increase of crop production, it was necessary to optimize utilization of transgenic technology. Key words: Gene transformation, Expression control, Antibiotic resistance